METHODS AND RESULTS OF APPLICATION OF THE NEUTRON DIFFRACTOMETRY IN THE EARTH SCIENCES: A REVIEW - Nikitin A.N.; Ivankina T.I. (My University, 2003)
Fundamental advantages of the neutron methods, that are based on the phenomenal properties of the neutron allow to extend the number of problems to be resolved in the solid-state physics, in geology and in geophysics, are analyzed in detail. A definition is given in the review to the crystallographic textures and emphasis was placed on the fact that the preferred orientation of the crystal lattices of the rock forming minerals as one of the main factors that controls the rock anisotropy, is an inherited property, acquired as a result of magmatism and metamorphism and other processes that governed the Earth's lithosphere formation. New results of investigation of the rock textural regularities and hence peculiarities of physical properties, such as behavior and anisotropy of the elastic wave velocities at high hydrostatic pressures, piezoelectric properties of some rocks as well as magnetic and thermal properties, are described. The review shows examples of application of the neutronography data along with other physical and petrophysical methods used to resolve fundamental problems in geology and in geophysics, such as reconstruction of the deformations and strains in the lithosphere and studies of the metamorphic, geodynamic and evolutionary processes addressed to data on structures of the deep-seated samples (xenoliths, amphibolites and gneiss taken from superdeep boreholes). Results of investigation of abnormal properties of some rocks which appear at a high temperature and pressure and possibilities of their application for the physics of destruction and for development of the earthquake models are discussed.
Keywords: NEUTRON DIFFRACTOMETRY; SOLID-STATE PHYSICS; NEUTRONOGRAPHY DATA; CRYSTALLOGRAPHIC TEXTURES